Poly(acrylamide-co-acrylic acid) synthesized, moxifloxacin drug-loaded hydrogel: Characterization and evaluation studies - Madhusudana Thippeswamy, Mamatha Ganjeenahalli Puttagiddappa, Demappa Thippaiah, Nayak Devappa Satyanarayan (Journal of Applied Pharmaceutical Science, 2021)
Sustained and controlled drug release has become the most attractive research work for obtaining a better drug delivery system with reliability, performance, and safe drug release in the modern pharmaceutical drug delivery design. In this view, different polymers in controlled drug delivery applications are very useful. Therefore, using copolymerization by free-radical crosslinking and methylenebisacrylamide as the crosslinker with potassium persulfate and sodium metabisulfite as initiators, we synthesized poly(acrylamide-co-acrylic acid) hydrogels. The synthesized hydrogels were characterized by FTIR, TGA, SEM, swelling, and in-vitro drug release studies which were carried out. The hydrogel swelling analysis was analyzed using buffer solutions at varying pH and temperature levels. Drug release was investigated using moxifloxacin hydrochloride as a model drug. The drug release data indicate that after 5 hours, the drug release was found to be 18% at acidic pH 1.2 and 99% at alkaline pH 7.4, and it followed the Higuchi model.
Keywords: Smart hydrogel, acrylic acid, acrylamide, drug delivery, moxifloxacin